Delegated Investment Decisions and Private Benefits of Control - Baldenius, Tim (The Accounting Review, 2003)
This paper studies the capital budgeting process in a setting where a manager is privately informed about the profitability of an investment project and enjoys nonpecuniary benefits of control (“empire benefits”). I characterize the optimal required rate of return and show that a delegation scheme with residual income-based compensation can replicate the benchmark performance achieved under centralization. The main result of the paper is that the optimal capital charge rate for computing residual income always exceeds the required rate of return as a result of empire benefits. This highlights the necessity for future empirical studies on capital budgeting to distinguish between alternative forms of hurdle rates. Contrary to conventional wisdom, I further show that if compensation contracts are derived endogenously, then the shareholders will ultimately benefit from the manager's empire benefits even under asymmetric information.